Thermal engineering of FAPbI3 perovskite material via radiative thermal annealing and in situ XRD - Pool V.L.; Dou B.; Van Campen D.G.; Klein-Stockert T.R.; Barnes F.S.; Shaheen S.E.; Ahmad M.I.; Van Hest M.F.A.M.; Toney M.F. (My University, 2025)
Lead halide perovskites have emerged as successful optoelectronic materials with high photovoltaic power conversion efficiencies and low material cost. However, substantial challenges remain in the scalability, stability and fundamental understanding of the materials. Here we present the application of radiative thermal annealing, an easily scalable processing method for synthesizing formamidinium lead iodide (FAPbI3) perovskite solar absorbers. Devices fabricated from films formed via radiative thermal annealing have equivalent efficiencies to those annealed using a conventional hotplate. By coupling results from in situ X-ray diffraction using a radiative thermal annealing system with device performances, we mapped the processing phase space of FAPbI3 and corresponding device efficiencies. Our map of processing-structure-performance space suggests the commonly used FAPbI3 annealing time, 10 min at 170 °C, can be significantly reduced to 40 s at 170 °C without affecting the photovoltaic performance. The Johnson-Mehl-Avrami model was used to determine the activation energy for decomposition of FAPbI3 into PbI2. © The Author(s) 2017.